Monitoreo del Clima Espacial desde Colombia mediante Radio-receptores Butterworth de Orden Superior - Jaramillo Alvarado, Andrés Felipe; Galvis Rodriguez, Hamilton David; Quintero Salazar, Edwin Andrés (Ingeniería, 2017)
Context: Solar flares and coronal mass ejections release great amounts of radiation to the outer space, altering the electrical properties of external layers in earth’s atmosphere. The set of phenomena derived from this interaction is known as space weather, and its consequences include failures in the geolocation systems, telecommunications, satellite based operations, spatial tracking, radio navigation and overload of electrical network. Method: This paper presents the development of a radio receptor enabling monitoring of space weather from Colombia. A novel methodology to design analog high-order Butterworth filters is described, based on the parallel interconnection of filtering banks of first and second order, yielding the realization of the desired transfer function. These filters are then used to build a radio receptor to monitor the mentioned solar activity. Results: The radio receptor was installed in a space weather monitoring station in Colombia, specifically in the Astronomical Observatory of the Universidad Tecnológica de Pereira (OAUTP), becoming operational on December 2015. From that date, the radio receptor has been registering solar activity uninterruptedly; and it has been able to detect four powerful solar explosions of class C, registered on the days 15, 16 and 17th in the month of April 2016. The received signals are sent to the Stanford Solar Center of Stanford University, with the code UTP 0383. Conclusions: The newly developed radio telescope is enabling the Astronomical Observatory OAUTP to monitor space weather and solar activity, sensing and registering such information in global publicly available repositories. No other radio receptors of this kind are currently operating from equatorial countries, a region on Earth were the effects of solar activity may lead to new insights in understanding this phenomena. Besides, we anticipate that the designed high-order filters may have application as well in instruments for sensing biomedical electrical signals.